1993
DOI: 10.1073/pnas.90.19.9066
|View full text |Cite
|
Sign up to set email alerts
|

An interdigitated columnar mosaic of cytochrome oxidase, zinc, and neurotransmitter-related molecules in cat and monkey visual cortex.

Abstract: There is considerable physiological evidence for the compartmentalization of mammalian visual cortex into functional columnar modules, representing features of visual information processing such as eye and orientation specificity.However, anatomical markers of visual cortical compartmentalization have been described only for primate visual cortex. In this report, we describe an interdigitated mosaic of four neuroactive molecules which demarcate two distinct columnar systems in the kitten visual cortex. Seroton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
35
1
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 24 publications
2
35
1
1
Order By: Relevance
“…In the cat, the relationship between the CO staining in the upper layers and the ocular dominance columns is unclear (Dyck and Cynader, 1993;Murphy et al, 1995;Boyd and Matsubara, 1996). In the squirrel monkey, we found no correspondence between the patches and the ocular dominance columns.…”
Section: Discussioncontrasting
confidence: 41%
“…In the cat, the relationship between the CO staining in the upper layers and the ocular dominance columns is unclear (Dyck and Cynader, 1993;Murphy et al, 1995;Boyd and Matsubara, 1996). In the squirrel monkey, we found no correspondence between the patches and the ocular dominance columns.…”
Section: Discussioncontrasting
confidence: 41%
“…The distribution of serotonergic receptors in cat visual cortex also changes in an age-dependent, regional, and laminar-specific manner (3). The most striking and specific pattern of developmentally regulated expression is the distribution of 5-HT 2C receptors into patches that separate layer IV of area 17 into 5-HT 2C receptor-rich and receptor-poor zones (3,4). A relationship to plasticity is suggested by the findings that monocular enucleation or dark rearing imposed early in life prevents the appearance of the patches (5), whereas in vivo studies have shown that blockade of the 5-HT 2C receptor class affects visual cortical activity-dependent plasticity (6,11).…”
Section: Discussionmentioning
confidence: 99%
“…1 summarizes autoradiographic and histochemical studies showing that, during the critical period, the kitten visual cortex transiently expresses a number of neurochemical markers in a columnar fashion. This columnar, biochemical architecture consists of two sets of complementary columns: one set is enriched in 5-HT 2C and 5-HT 2A receptors along with synaptic zinc, whereas the other expresses increased levels of CO and acetylcholinesterase (3,4). Among over 30 neurotransmitter receptors that have been studied within the visual cortex (1,2), only the 5-HT receptors noted above have been found to concentrate into columns within the developing cortex.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To test this hypothesis, Kojic et al (7) took advantage of the fact that this 5HT receptor patch system is complementary to another system of patches: the cytochrome oxidase (CO) blobs in layer II͞III. The CO blobs in layer II͞II are in register with 5HT receptor-poor patches in layer I V, whereas interblobs are on top of 5HT receptor-rich patches (15). Post hoc patch identification revealed that 5HT promoted the induction of LTP in 5HT2C receptor-rich patches and LTD in the receptor-poor patches (7).…”
mentioning
confidence: 99%